Lipoprotein(a) in Cardiovascular Diseases. (30th December 2012) - Malaguarnera, Michele; Vacante, Marco; Russo, Cristina; Malaguarnera, Giulia; Antic, Tijana; Malaguarnera, Lucia; Bella, Rita; Pennisi, Giovanni; Galvano, Fabio; Frigiola, Alessandro
Abstract : Lipoprotein(a) (Lp(a)) is an LDL-like molecule consisting of an apolipoprotein B-100 (apo(B-100)) particle attached by a disulphide bridge to apo(a). Many observations have pointed out that Lp(a) levels may be a risk factor for cardiovascular diseases. Lp(a) inhibits the activation of transforming growth factor (TGF) and contributes to the growth of arterial atherosclerotic lesions by promoting the proliferation of vascular smooth muscle cells and the migration of smooth muscle cells to endothelial cells. Moreover Lp(a) inhibits plasminogen binding to the surfaces of endothelial cells and decreases the activity of fibrin-dependent tissue-type plasminogen activator. Lp(a) may act as a proinflammatory mediator that augments the lesion formation in atherosclerotic plaques. Elevated serum Lp(a) is an independent predictor of coronary artery disease and myocardial infarction. Furthermore, Lp(a) levels should be a marker of restenosis after percutaneous transluminal coronary angioplasty, saphenous vein bypass graft atherosclerosis, and accelerated coronary atherosclerosis of cardiac transplantation. Finally, the possibility that Lp(a) may be a risk factor for ischemic stroke has been assessed in several studies. Recent findings suggest that Lp(a)-lowering therapy might be beneficial in patients with high Lp(a) levels. A future therapeutic approach could include apheresis in high-risk patients in order to reduce major coronary events.